Preliminary Experiences With Robot-Assisted Choledochal Cyst Excision Using the Da Vinci Surgical System in Children Below the Age of One - Xie, Xiaolong; Wu, Yang; Li, Kewei; Ai, Chengbo; Wang, Qi; Wang, Chuan; Chen, Jing; Xiang, Bo (Frontiers in Pediatrics, 2021)
The purpose of this study is to introduce our preliminary experiences with using the da Vinci surgical system to treat choledochal cysts in children under one year old and discuss the application of this robotic assisted surgery. We retrospectively analyzed all available clinical data of children below the age of one who underwent surgery for choledochal cysts using the da Vinci robotic surgical system between January 2015 and December 2020. Data collection mainly included demographic information, imaging data, perioperative details and postoperative outcomes. Ten patients were included in this study. The average patient age was 8.5 months and the average weight was 9.11 kilograms. Half of these patients suffered from abdominal pain, while 30% exhibited vomiting and 10% jaundice. Eight of them were type Ia and two were Ic. The average operation time among the patients was 219.5 min. None of the ten patients had to receive a blood transfusion or conversion. The average time of the patients’ subsequent fluid diet was 3.28 days and the solid diet was 3.76 days. Meanwhile, the average length of hospital stay was 7.6 days. All ten patients recovered and were eventually discharged. We believe that the da Vinci surgical system is a safe and feasible form of treatment for choledochal cysts in children less than one year old.